Conserving nature under neoliberalism in Europe: The Greenbelt of Fennoscandia project - Florin, Ian (2017)
Recent years have witnessed a growing debate regarding the appropriate way to design and manage protected areas throughout the globe. While the venerable fortress conservation paradigm has been strongly criticized, supposedly more integrative and participatory approaches that aimed to replace it have come under considerable criticisms over the last two decades, notably concerning their incapacity to achieve consequential conservation outcomes. In this context, large-scale conservation corridors - seemingly capable to mitigate the effects of habitat fragmentation on key ecosystem processes – have increasingly gained prominence with scientists and protected areas practitioners. As recently as during the 2016 IUCN World Parks Congress, large-scale corridors have been promoted as scientifically sound, collaborative and profitable responses to threats to biodiversity. Building on literature in political ecology and geography, my thesis wants to analyze how and why individuals and collectives frame, shape and use large-scale corridors. Using the Greenbelt of Fennoscandia as a case study, I examine how stakeholders select their arguments – together with concepts and moralities that underlie them – regarding the project and why they do so. Drawing on semi-structured interviews as well as a desk study of stakeholders' claims, I examine how conservation discourses and practices are justified – in Boltanski & Thévenot's terms – and expressed, through antipolitics. I argue that these justifications related to nature conceptions or economic rationality contribute to what Büscher calls fictitious conservation, that occurs when conservation goals are replaced by the pursuit of competitive advantage through consensus making and marketing.